Bound by barriers: demystifying the constraints on an elevated Kuwait-Türkiye co-operation in the defence realm - Ali Bakir (17917703) (2025)
In the past decade, several Gulf Cooperation Council (GCC) states have diversified their defence partnerships and intensified local defence-industry initiatives, increasingly considering Türkiye as a viable option. However, Kuwait's position differs from that of its Gulf counterparts in three key ways. First, Kuwait is less inclined to enhance its security and defence ties with Türkiye compared to the UAE, Qatar, and Saudi Arabia. Second, unlike these nations, Kuwait shows little interest in developing a domestic defence industry. Third, although there have been recent positive developments in Kuwaiti-Turkish defence relations, these ties remain limited compared to the robust political and economic connections between the two countries and the extensive defence relationships other GCC states have cultivated with Türkiye. To address the question of why, our paper draws on small state theories, utilizing a mixed-methods approach that includes interviews and communications with officials and experts, as well as analysis of primary sources. Other Information Published in: Defense & Security Analysis License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14751798.2025.2549198